Tributação sobre "venda direta" pela previdência social - Pereira, Maria Elisa Fudaba Curcio (2015)
Taxation on "direct sales" activities by Social Security is an issue that has provoked debate among legal experts and policy makers. Given this, this master's thesis is the result of research focused on the environment of direct sales or mail order. More specifically on the way of functional relationship between sales representatives and companies from the perspective of the Brazilian System of Social Security. Based on the absence of employment contract, the legal relation between direct sales companies and representatives defines its conditions as independent vendors. This was the starting point of the problematic, since these individual vendors are not included in the constitutional social protection of Social Security.